90/90 Bicortical, double-loop, interosseous wiring for fixation of transverse and short oblique metacarpal shaft fractures. Issue 2 (March 2019) - Afifi, Ahmed; Dobal, M. Hussein; Mahmoud, Mostafa; Moharram, Ashraf N.
Abstract : Background: The purpose of this study was to determine the effectiveness of 90/90 interosseous wiring for fixation of transverse and short oblique metacarpal shaft fractures on early motion. Methods: This prospective study was conducted at an academic Level 1 trauma Center from 2015 to 2017. The study included 20 patients (16 males and 4 females). The mean age was 27.3 yr (range, 12 to 44 yr). The dominant hand was affected in 10 patients, and the nondominant hand was affected in the other 10 patients. Regarding the fracture pattern, 17 were transverse and three were short oblique fractures. The mean follow-up period was 6 mo (range, 4 to 8 mo). Patients were assessed for union (clinically and radiographically), range of motion (total active motion [TAM] and total active flexion [TAF]), hand grip strength, and patient-reported outcome using the quick-Disabilities of the Arm, Shoulder and Hand (DASH) questionnaire. Results: All patients achieved union after a mean of 7 wk (range, 6 to 8 wk). The mean TAF was 246 degrees (range, 150[Combining Ring Above] to 260 degrees). TAM was excellent in 13 digits and good in seven digits. The mean grip strength was 90.20% (range, 61.53% to 100%) of the unaffected side. The mean quick-DASH score was 2.72 (range, 0 to 20.45). Conclusions: The interosseous wiring technique is an effective method of fixation that can be used alone for transverse or short oblique fractures of the metacarpal and can permit early hand mobilization postoperatively without loss of reduction.